Epidemiology and risk factors of multidrug‐resistant bacteria in respiratory samples after lung transplantation. Issue 1 (30th January 2016) - Tebano, G.; Geneve, C.; Tanaka, S.; Grall, N.; Atchade, E.; Augustin, P.; Thabut, G.; Castier, Y.; Montravers, P.; Desmard, M.
Abstract: Background: Multidrug‐resistant (MDR) bacteria are a growing concern worldwide. The aim of this study was to describe the epidemiology and risk factors of MDR bacteria detected in respiratory invasive samples during hospitalization in the intensive care unit (ICU) after lung transplantation (LT). Methods: This study was based on a retrospective analysis of 176 patients hospitalized in the ICU after LT in 2006–2012. Respiratory invasive samples were performed according to a routine protocol. MDR pathogens were defined according to in vitro susceptibility tests. Results: A total of 1176 bacteria were cultured. Susceptibility testing was performed on 1046 strains and 404 (39%) MDR were detected in 90 (51%) patients. Pseudomonas aeruginosa, coagulase‐negative staphylococci, and Enterobacteriaceae (mainly Enterobacter species) were the most common MDR pathogens. On multivariate analysis, an ICU stay >14 days, presence of a tracheostomy, and previous exposure to broad‐spectrum antibiotics were associated with MDR acquisition (odds ratio [OR] 3.7; 95% confidence interval [1.69–8.12]; OR 3.28 [1.05–10.28]; and OR 2.25 [1.17–4.34], respectively). We consistently observed an increasing emergence of resistance to several antibiotics, from week 1 to week 4 of ICU hospitalization: for ticarcillin, piperacillin–tazobactam, ceftazidime, imipenem/cilastatin, amikacin, and ciprofloxacin in P. aeruginosa ; and for piperacillin–tazobactam, cefepime, and amikacin in Enterobacteriaceae. Conclusion: A large proportion of MDR bacteria are detected on respiratory invasive samples in LT patients, and the risk of their emergence is mainly determined by the previous exposure to broad‐spectrum antibiotics and the length of ICU stay. Adequate treatment requires broad‐spectrum empiric antibiotic therapy.